A Case of Endobronchial Lipoma. Issue 4 (1999) - Iwabuchi, Hiroshi; Kamura, Tetsuo; Tanaka, Michio; Kato, Harubumi
Abstract : Endobronchial lipomas are very rare tumors originating from the tracheo-bronchial wall. We have experienced a case of endobronchial lipoma which was found at the orifice of the left lower lobe bronchus and obstructive pneumonia distal to it. Left lower lobectomy was performed, and the patient has been well without any symptoms so far. Endobronchial lipomas are histologically benign tumors, but more than half of the reported cases underwent lobectomy or pneumonectomy due to the presence of varying degrees of irreversible peripheral lung damages.